2013
DOI: 10.1074/jbc.m113.501346
|View full text |Cite
|
Sign up to set email alerts
|

Active Glutaminase C Self-assembles into a Supratetrameric Oligomer That Can Be Disrupted by an Allosteric Inhibitor

Abstract: Background: GAC supplies for increased metabolic needs of tumors because of exclusive localization and kinetic properties. Results: Higher than tetramer oligomers are the active form in in vitro and in cellular assays. Bis-2-(5-phenylacetamido-1,3,4-thiadiazol-2-yl)ethyl sulfide disrupts oligomers. Conclusion: A novel molecular mechanism for GAC activation is proposed. Significance: The data affect the development of therapies targeting GAC in tumors, with emphasis on allosteric inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(143 citation statements)
references
References 32 publications
13
125
2
3
Order By: Relevance
“…This study also showed that GAC could exist not only as a dimer or tetramer, but also as an elongated higher order oligomer, with oligomerization increasing as a function of phosphate concentration [70]. This latter result was also reported by Ferreira and coworkers, who demonstrated the filament-like nature of the higher order GAC oligomer via electron microscopy [66]. This report also indicated the critical nature of a short loop, from Leu 316 to Leu 321 of the human enzyme, which the authors called a 'gating loop' (Figure 5B).…”
Section: Gls 5ǵsupporting
confidence: 70%
See 1 more Smart Citation
“…This study also showed that GAC could exist not only as a dimer or tetramer, but also as an elongated higher order oligomer, with oligomerization increasing as a function of phosphate concentration [70]. This latter result was also reported by Ferreira and coworkers, who demonstrated the filament-like nature of the higher order GAC oligomer via electron microscopy [66]. This report also indicated the critical nature of a short loop, from Leu 316 to Leu 321 of the human enzyme, which the authors called a 'gating loop' (Figure 5B).…”
Section: Gls 5ǵsupporting
confidence: 70%
“…The structures of both GLS and LGA have been determined by x-ray crystallography, although substantially more effort has been devoted to describing GLS than LGA. Table 3 shows the details of the currently available mammalian glutaminase crystal structures [37,[63][64][65][66][67][68]. The constructs used for crystallography include the isolated glutaminase catalytic domain (e.g., 3CZD or 3VP1) and the entire biologically processed form of the enzyme (e.g., 3UNW or 5FI7), and structures have been determined with glutamine, glutamate or assorted inhibitors bound.…”
Section: Gls 5ǵmentioning
confidence: 99%
“…Its activity is increased by NF-κB (19), and its expression is induced by MYC, whose overexpression rendered transformed cells addicted to glutamine (9,12,13). GLS is expressed as a long mRNA splice variant, KGA, or a shorter form, GAC, which is increased in cancers relative to normal tissues (19,24). siRNA-mediated knockdown of GLS slowed the growth of several different cancer types (13,17,19,(25)(26)(27), suggesting that pharmacological inhibition of GLS offers a potential therapeutic approach for treating cancer.…”
Section: Resultsmentioning
confidence: 99%
“…We found that BPTES inhibited P493 lymphoma cell growth by causing DNA replication defects that triggered cell death and fragmentation. Ectopic overexpression of a GLS mutant, which resists inhibition by BPTES (24), could rescue P493-cultured cells or xenografts from BPTES-mediated growth inhibition, attesting to an on-target effect of BPTES. We further corroborated animal genetic and pharmacological studies using a human-specific Vivo-Morpholino that induces nonsensemediated GLS mRNA decay and found that P493 tumor xenograft growth in mice could be markedly and specifically inhibited only by Vivo-Morpholino directed at human GLS, but not by that directed at mouse Gls.…”
Section: Introductionmentioning
confidence: 99%
“…The GAC K320A allele encodes a fiber-prone super-active form of GAC that is insensitive to BPTES. 21 Expression of the GAC K320A mutant in OCI-AML2 cells promoted resistance to CB-839, as no changes were observed in the OCR (Figure 2F, right). Overall, these findings indicate that targeting glutaminolysis impacts mitochondrial respiration and the OCR.…”
Section: Gac Protein Is Prominently Expressed In Aml and Modulates Thmentioning
confidence: 99%